Rising Mortality From Alcohol-Associated Liver Disease in the United States in the 21st Century - Moon, Andrew M.; Yang, Jeff Y.; Barritt, A. Sidney; Bataller, Ramon; Peery, Anne F. (The American journal of gastroenterology, 2020)
In contrast with other developed nations, life expectancy is decreasing in the United States, in part due to increasing mortality from alcohol-associated liver disease (ALD). Up-to-date estimates of ALD mortality are necessary for setting public health priorities to reverse this concerning trend. We therefore aimed to assess current (2017) estimates of ALD mortality and temporal trends from 1999 to 2017. Using national data from the Centers for Disease Control and Prevention, we analyzed stratified ALD mortality rates between 1999 and 2017. We determined the age-adjusted death rates, stratified by sex and categorized by age, race/ethnicity, urbanization, and census region. We also identified statistically significant changes in the annual rate difference (ARD), annual percentage change (APC), and average APC in ALD mortality. In 2017, mortality from ALD was higher than any other year since 1999 with age-adjusted rates of 13.1 per 100,000 (95% confidence interval [CI] 12.9-13.3) in men and 5.6 per 100,000 (95% CI 5.4-5.7) in women. Mortality was highest among men and women who were middle aged, Native American, and from rural areas. Since 2006, ALD mortality has increased in almost every age group and race with the exception of non-Hispanic black men. Absolute increases in mortality rates have been particularly pronounced in Native American women (2005-2017 ARD 0.8, 95% CI 0.6-0.9), non-Hispanic/white men (2006-2017 ARD 0.4, 95% CI 0.3-0.4), and non-Hispanic/white women (2013-2017 ARD 0.4, 95% CI 0.3-0.5). Mortality from ALD is increasing over time in most demographic groups. Increased effort is needed to develop targeted public health strategies to address high and increasing ALD mortality.